PERANCANGAN GEDUNG PUSAT BADAN EKONOMI KREATIF INDONESIA DI SURABAYA TEMA OUT OF THE BOX - Wibowo, Gavrila; Hendra, Failasuf Herman; Laksmiyanti, Dian Pramita Eka (Aksen : Journal of Design and Creative Industry, 2020)
creative economy becomes one of priorities which is feasible to develop because the strength of creativeeconomy does not depend on the exploitation of natural resources instead of human resources. Art works,architecture, technology innovation, animation, and other creative products are derived from creativeideas of human thoughts. These phenomena have encouraged people’s enthusiasm to create innovationand require support from Creative Economy Agency which is specifically responsible for monitoring andguiding the creative economy.The Central Building of Creative Economy Agency is planned and designedin Surabaya as an effort to provide facilities for developing the Office of Creative Economy Agency.The facilities are designed in such a way so as to support Surabaya as the metropolitan city which isenvironmentally friendly and interesting for business doers particularly start-up business. Designing the buildingarchitecture is carried out through a series of phases beginning from project identification, precedent study,design program, concept, and development. The approach of Out of the Box theme is used as the point ofview which is different from the usual in terms of land order, shape, and space configuration. So as to producebuildings Is carried out by continuing and changing or transforming the office building from the standardized andrigid characters into flexible and relaxed office without altering the culture of behavior inside. It does not leave theusers’ culture or habit including those who want to work autonomously. Keywords: Sustainable Architecture, Creative Economy, Out Of the Box